2019
DOI: 10.1002/chem.201805837
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Insights into the Anaerobic Degradation of 4‐Isopropylbenzoyl‐CoA in the Denitrifying Bacterium Strain pCyN1

Abstract: The constitutions and absolute configurations of two previously unknown intermediates, (1S,2S,4S)‐2‐hydroxy‐4‐isopropylcyclohexane‐1‐carboxylate and (S)‐3‐isopropylpimelate, of anaerobic degradation of p‐cymene in the bacterium Aromatoleum aromaticum pCyN1 are reported. These intermediates (as CoA esters) are involved in the further degradation of 4‐isopropylbenzoyl‐CoA formed by methyl group hydroxylation and subsequent oxidation of p‐cymene. Proteogenomics indicated 4‐isopropylbenzoyl‐CoA degradation involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Notably, the genome of Ar. petrolei ToN1 T does not contain genes for a 4-isopropylbenzoyl-CoA-specific reductase [Küppers et al, 2019], agreeing with its incapacity to anaerobically degrade the aromatic monoterpene p-cymene [Rabus et al, 2019]. These differences in the genetic equipment and thereof resulting range of utilizable monoterpenes between Ar.…”
Section: Catabolic Networkmentioning
confidence: 78%
See 1 more Smart Citation
“…Notably, the genome of Ar. petrolei ToN1 T does not contain genes for a 4-isopropylbenzoyl-CoA-specific reductase [Küppers et al, 2019], agreeing with its incapacity to anaerobically degrade the aromatic monoterpene p-cymene [Rabus et al, 2019]. These differences in the genetic equipment and thereof resulting range of utilizable monoterpenes between Ar.…”
Section: Catabolic Networkmentioning
confidence: 78%
“…(iii) Modified β-oxidation yielding the respective pimeloyl-CoA derivate is then presumably conducted by the BadH-K enzymes as recently proposed for Ar. aromaticum pCyN1 [Küppers et al, 2019]. In case of limonene the exocyclic double bond is probably retained along the hypothesized pathway to the level of the pimeloyl-CoA derivate (Fig.…”
Section: Catabolic Networkmentioning
confidence: 99%
“…3). In addition to this peripheral module, protein components of the downstream conversion, viz., Thauera-type class I benzoyl-CoA reductase followed by Rhodopseudomonas-type β-oxidation (Küppers et al, 2019), also revealed a rather high specificity for these monoterpenes. This, in turn, indicates a concerted transcriptional regulation, even though the respective genes are scattered across the 'p-cymene' gene cluster (Fig.…”
Section: Substrate-specific Regulation Of the Anaerobic Degradation N...mentioning
confidence: 97%
“…The presence of these compounds suggests a degradation pathway of α-terpinene (6a) that is similar to the known degradation pathway of p-cymene (1). [23,24] In addition, p-isopropylbenzoyl-CoA (4b) was abundant in the culture extracts (unpublished results; Rabus, Wilkes, Christoffers, and co-workers), which is not necessarily expected to occur as an intermediate during anaerobic degradation of α-terpinene (6a). Based on these findings and taking into account the possibility of a disproportionation reaction, a pathway for the degradation of α-terpinene (6a) is proposed (Scheme 1, steps e-p), including a disproportionation of 4-isopropyl-1,3-cyclohexadiene-1-carbonyl-CoA (9b) to p-isopropylbenzoyl-CoA (4b) and 4isopropyl-1-cyclohexene-1-carbonyl-CoA (10a) (Scheme 2, Equation 2).…”
Section: Introductionmentioning
confidence: 96%
“…After further functional group interconversions (steps f, m, n) the ring is cleaved to furnish 3-isopropylpimeloyl-CoA (11, step o). [23,24] Other investigations showed that the disproportionation of dienoyl-CoA 14 to benzoyl-CoA (16) and enoyl-CoA 15 is catalyzed by a tungsten-containing class II BCR under artificial conditions (Scheme 2, Equation 1) as well as by Ferroglobus placidus cell extracts by a so far unknown enzyme. [25,26] Latest investigations in our laboratories on methylated extracts of bac-terial cultures of strain pCyN1 grown on α-terpinene (6a) led to the identification of four compounds as their corresponding methyl esters, namely 4-isopropyl-1,5-cyclohexadiene-1-carbonyl-CoA (9b), 4-isopropyl-1-cyclohexene-1-carbonyl-CoA (10a), 2-hydroxy-4-isopropylcyclohexane-1-carbonyl-CoA (13) and 3isopropylpimeloyl-CoA (11) (unpublished results; Rabus, Wilkes, Christoffers and co-workers).…”
Section: Introductionmentioning
confidence: 99%